The Dynamics of Exchange Rate, Inflation, and Trade Balance in Indonesia - Wicesa, Nayaka Artha; Widiyono, Yon; Kaluge, David (Jurnal Ekonomi Kuantitatif Terapan; 2021: Vol. 14, No. 2, Agustus 2021 (pp.243-431)DO - 10.24843/JEKT.2021.v14.i02.p03, 2021)
Balance of trade has become an essential indicator for economic activities, particularly in countries adopting the open economy. During the last two decades, Indonesia has had trade surplus. The open economy has created dynamics in macroeconomic variables. The purpose of this research is to identify any dynamics between exchange rate, inflation, and balance of trade in Indonesia. Using the Autoregressive Distributed Lag, this study finds the dynamics between the said variables. In the short run, there are causalities between exchange rate and balance of trade, exchange rate and inflation, and balance of trade and inflation. In addition, J-Curve also occurred in Indonesia, where depreciation in exchange rate gradually improves the country’s balance of trade in the second and fourth quarters. Keywords : Exchange Rate, Inflation, Balance of Trade, Autoregressive Distributed Lag JEL Classification: F1, F4, C1